2023
DOI: 10.3390/recycling8030046
|View full text |Cite
|
Sign up to set email alerts
|

Microfactory Design for Valorization of E-Waste Plastics (Acrylonitrile-Butadiene-Styrene, Polycarbonate, and Polypropylene) on Additive Manufacturing Sector

Abstract: Less than half of e-waste plastics are sorted worldwide, and this rate is likely to decline as major processing countries have banned importation of e-waste plastics. This forces the development of decentralized processing facilities, also known as microfactories. The present work investigates the recyclability of different grades of acrylonitrile-butadiene-styrene (ABS) copolymer, polycarbonate, and polypropylene, which were found to be very abundant in a recycling site in the UK. The determination of the mat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In the UK, it has been also found in electronic wastes, while during the COVID-19 pandemic it was used to produce protective masks. Health industry wastes need to be sterilized before they can be recycled such as common urban wastes [52][53][54][55]. PP is mainly used as a single-end plastic, studies have shown that tensile properties have a steady behavior despite the common perception of plastic downgrading that has been verified for other types [56,57].…”
Section: Industrial Polymeric Wastementioning
confidence: 99%
See 2 more Smart Citations
“…In the UK, it has been also found in electronic wastes, while during the COVID-19 pandemic it was used to produce protective masks. Health industry wastes need to be sterilized before they can be recycled such as common urban wastes [52][53][54][55]. PP is mainly used as a single-end plastic, studies have shown that tensile properties have a steady behavior despite the common perception of plastic downgrading that has been verified for other types [56,57].…”
Section: Industrial Polymeric Wastementioning
confidence: 99%
“…PP is mainly used as a single-end plastic, studies have shown that tensile properties have a steady behavior despite the common perception of plastic downgrading that has been verified for other types [56,57]. Recycled PP has shown property stability during recycling processes making it, despite the warping issues, a promising material for future investigation and valorization [53,58]. The amount of electronic waste has been rapidly increasing in the last decade, with ABS being the main polymer that can be extracted from it.…”
Section: Industrial Polymeric Wastementioning
confidence: 99%
See 1 more Smart Citation